Instantiation of a classification system framework that facilitates reuse - Lopes, Sérgio F. (2007)
Frameworks are a key technology to reduce software development costs and shorten the time-to-market. However, framework complexity presents reuse problems that limit its success as an application development alternative. Therefore, it has been widely recognized that is necessary to effectively communicate frameworks and provide appropriate tool support. Although advancements have been made in these directions, difficulties still endure. We argue the problem should also be addressed at another level – the framework model. Moreover, both the framework documentation and the level of support that tools can provide are decisively dependent on the considered framework model. In this paper, we present our proposed framework model and the respective supporting notation. We discuss their application in the design and description of a Classification System Framework. Then we describe how the framework can be reused based on the proposed description technique. This case study illustrates how the proposed model and description help to alleviate difficulties of framework reuse.